11th U.S./North American Mine Ventilation Symposium 2006 : proceedings of the 11th U.S./North American Mine Ventilation Symposium : the Pennsylvania State University, University Park, Pennsylvania, USA : 5-7 June 2006 /: proceedings of the 11th U.S./North American Mine Ventilation Symposium : the Pennsylvania State University, University Park, Pennsylvania, USA : 5-7 June 2006. (2006) - Unknown
No abstract available